Aview on pediatric airway management: a cross sectional survey study - SARAÇOĞLU, AYTEN (My University, 2022)
© 2022 Edizioni Minerva Medica. All rights reserved.BACKGROUND: This survey aimed to investigate routine practices and approaches of clinicians on pediatric airway in anesthesia and intensive care medicine. METHODS: A 20-question multiple-choice questionnaire with the possibility to provide open text answers was developed and sent. The survey was sent to the members of European Airway Management Society via a web-based platform. Responses were analyzed thematically. Only the answers from one representative of the pediatric service of each hospital was included into the analysis. RESULTS: Among the members, 143 physicians responded the survey, being anesthesiologists (83.2%), intensivists (11.9%), emergency medicine physicians (2.1%), and (2.8%) pain medicine practitioners. Astraight blade was preferred by 115 participants (80.4%) in newborns, whereas in infants 86 (60.1%) indicated a curved blade and 55 (38.5%) a straight blade. Uncuffed tracheal tube were preferred by 115 participants (80.4%) in newborns, whereas 24 (16.8%) used cuffed tubes. Approximately 2/3 of the participants (89, 62.2%) reported not to use routinely a cuff manometer in their clinical practice, whereas 54 participants (37.8%) use it routinely in pediatric patients. Direct laryngoscopy for routine pediatric tracheal intubation was reported by 127 participants (88.8%), while 16 (11.2%) reported using videolaryngoscopes routinely. Interestingly, 39 (27.3%) had never performed neither videolaryngoscopy nor flexible bronchoscopy in children. These results were significantly less in hospitals with a dedicated pediatric anesthesiologist. CONCLUSIONS: This survey on airway management in pediatric anesthesia revealed that the use of cuffed tubes and the routine monitoring of cuff pressure are rare. In addition, the rate of videolaryngoscopy or flexible optical intubation was low for expected difficult intubation. Our survey highlights the need for properly trained pediatric anesthesiologists working in-line with updated scientific evidence.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Airway management; Pediatris; Surveys and questionnaires